Public health response to large influx of asylum seekers: implementation and timing of infectious disease screening - Paula Tiittala; Karolina Tuomisto; Taneli Puumalainen; Outi Lyytikäinen; Jukka Ollgren; Olli Snellman; Otto Helve (BMC, 2018)
Abstract Background Infectious disease screening of migrants at increased risk is a feature of national infection prevention and control measures. Asylum seekers in Finland are offered screening of tuberculosis (TB), hepatitis B, human immunodeficiency virus infection (HIV) and syphilis based on individual risk assessment. We aimed to evaluate the public health response to a large influx of asylum seekers to Finland in 2015-2016 with respect to national guidelines on initial health services and infectious disease screening. Methods We used immigration and healthcare procurement data for all 38,134 asylum seekers to Finland during 2015-2016 to assess the implementation, timing and yields of infectious disease screening. Results The coverage of pulmonary TB screening was 71.6% [95% CI 71.1-72.0%] and that of hepatitis B, HIV or syphilis 60.6% [60.1-61.1%] among those eligible for screening. The estimated average delay from arrival to pulmonary TB screening was 74 days for adults and 43 days for children. Delay to hepatitis B, HIV and syphilis screening was 91 days for adults and 47 days for children. The seroprevalence of hepatitis B surface antigen positivity was 1.4% [95% CI 1.3-1.6%], HIV 0.3% [95% CI 0.1-0.4%] and Treponema pallidum specific antibodies 1.0% [95% CI 0.8-1.1%]. Data did not allow assessment of yields of pulmonary TB screening. Conclusions Up to one third  of asylum seekers were not reached by screening and screenings were delayed from target timeframes. Children, as a vulnerable population, were screened earlier than adults. To ensure higher screening coverage, infectious disease risks should be reassessed and screening completed at contacts to healthcare during the post-asylum phase of integration. The large influx of asylum seekers to Finland in 2015-2016 tested the country's public health preparedness. After action reviews of the public health response to the large migrant influx such as screening implementation can be used for evidence-based improvement of public health preparedness and guidelines for initial health services and infectious disease screening.